1980
DOI: 10.1097/00006842-198005000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Ego Defenses and Endocrine Responses in Women Prior to Breast Biopsy and Ten Years Later

Abstract: Thirty women with breast masses were evaluated psychologically and endocrinologically ten years ago while they were awaiting breast biopsy (3). Eight of these women proved to have benign fibrocystic disease and 22 had breast cancer. A significant (p < 0.05) positive correlation was found between extent of failure of psychological "defenses" and cortisol metabolite excretion rate in these 30 women. On follow-up, 12 women had died (11 with cancer and one who had had benign disease); 7 women were lost to follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Similarly to how CSE represent relatively stable ways of understanding the world, studies have shown that coping can be relatively stable over time, and thus reflect a coping style (e.g., Gorzynski et al, 1980). More specifically, coping style can be defined as "a repertoire of strategies available to cope with stressful encounters, specific for an individual" (Heszen-Niejodek, 1997, p. 343).…”
Section: Copingmentioning
confidence: 99%
“…Similarly to how CSE represent relatively stable ways of understanding the world, studies have shown that coping can be relatively stable over time, and thus reflect a coping style (e.g., Gorzynski et al, 1980). More specifically, coping style can be defined as "a repertoire of strategies available to cope with stressful encounters, specific for an individual" (Heszen-Niejodek, 1997, p. 343).…”
Section: Copingmentioning
confidence: 99%
“…Temporal reliability was demonstrated in a 10-year follow-up of 10 women studied by Katz, et al (1970). The follow-up produced ED ratings that correlated r = .90 with the original ratings (Gorzynski, et al, 1980). This high level of consistency was obtained despite the fact that the ratings were made by different sets of raters.…”
Section: Effectiveness Of Defensesmentioning
confidence: 76%
“…Since the 1950s, the cancer-prone personality described earlier, with its concomitant coping style of suppressed emo-Downloaded by [Deakin University Library] at 03:30 15 March 2015 tion, has been observed (LeShan, 1959;LeShan & Worthington, 1956). Longer-term survival has been correlated with the external expression of negative emotions toward one's illness and one's treating physicians, and shorter-term survival has been correlated with suppression and denial of psychological distress (Bacon, Renneker, & Cutler, 1952;Blumberg, West, & Ellis, 1954;Derogatis, Abeloff, & Melisaratos, 1979;Gorzinski et al, 1980;Rogentine, Fox, & VanKammen, 1978;Thomas, 1976;West, Blumberg, & Ellis, 1952). Some of this work, particularly that of Dcrogatis et al (1979), has been challenged because the research psycliologically assessed women at different points in time relative to diagnosis and treatment, thereby confusing responses to biological disease with the effects of treatment.…”
Section: Coping Styles As Prognostic Indicatorsmentioning
confidence: 99%